Consumers Perception ofEco-Friendly Products in Thoothukudi (International Journal of Food and Nutritional Sciences, 2022)
Eco-friendly productswhich are considered to be less harmful to the environment than its regular counterparts. If more people start buying eco-friendly products, pollution would not be so rampant, our planet would have a timeout to breathe and regenerate, and our families and communities would be healthier in the long term. Moreover, eco-friendly products are not only great for the environment, but also beneficial for human health. This present study is an endeavor to analyse consumer perception on eco-friendly products among the users of the eco-friendly product in Thoothukudi District. . The data has been collected from a total of 174 respondents in Thoothukudi District through a well-structured questionnaire. Eco–friendly product consumers are becoming more environmentally conscious and are demanding eco-friendly products from manufacturers, which leads to a sustainable environment.